Pembaruan Hukum Pencatatan Perkawinan di Indonesia Perspektif Maqasid Shari'ah - Masruhan Masruhan (IAIN Ponorogo, 2013)
Abstract: The role of marriage registration (recording) is important particularly in maintaining and protecting the rights of individuals to prove the marriage implementation. Registration of marriage, therefore, is governed by various related rules or regulation. Unfortunately, the registration of marriage is only as a normative one. Meanwhile, most Muslims do not obey the law of marriages arranged by the state because the law is ambiguous, having multi interpretations and difficult to implement. In fact, there are many negative effects emerging from marriage under the hands such as not getting the marriage certificate, and husband, wife and their children not being able to perform civil legal action against the genetic father who has left them. Therefore, marriage under the hand must be prevented with preventive, curative and anticipative measures. In order to produce a law that can respond to the changing demands of time, place, conditions and welfare of the spouses, the maqa>sid al - shari>ah approach (the purpose of the law) is eligible to apply . Therefore, the government should change the law of registration of marriages that are not relevant to the state of society so that society will feel suitable with the legal registration of the marriage.